2022
DOI: 10.1017/s2040174421000726
|View full text |Cite
|
Sign up to set email alerts
|

Maternal BMI, breastfeeding and perinatal factors that influence early childhood growth trajectories: a scoping review

Abstract: Obesity rates among children are rapidly rising internationally and have been linked to noncommunicable diseases in adulthood. Individual preventive strategies have not effectively reduced global obesity rates, leading to a gap in clinical services regarding the development of early perinatal interventions. The objective of this scoping review is to explore the relationship between maternal BMI and breastfeeding behaviors on child growth trajectories to determine their relevance in developing interventions aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The association between maternal preconception BMI and childhood weight outcomes may be mediated by early growth, which should be explored through mediation analyses in future studies. Furthermore, as the association with growth rate was most pronounced in the early months, and maternal preconception weight status has previously been associated with breastfeeding initiation and duration, 56 future studies might consider the potential mediating role of breastfeeding exclusivity and duration, which has previously been associated with child weight and growth 57 . Unfortunately, information regarding breastfeeding exclusivity was not obtained for the present cohort but will be collected prospectively.…”
Section: Discussionmentioning
confidence: 96%
“…The association between maternal preconception BMI and childhood weight outcomes may be mediated by early growth, which should be explored through mediation analyses in future studies. Furthermore, as the association with growth rate was most pronounced in the early months, and maternal preconception weight status has previously been associated with breastfeeding initiation and duration, 56 future studies might consider the potential mediating role of breastfeeding exclusivity and duration, which has previously been associated with child weight and growth 57 . Unfortunately, information regarding breastfeeding exclusivity was not obtained for the present cohort but will be collected prospectively.…”
Section: Discussionmentioning
confidence: 96%
“…In this context, many studies have linked individual factors or modalities to infant growth and development—including head circumference (reflecting both physical growth and brain development 12 , 13 ) and cognitive or behavioral outcomes (such as the Bayley Scales of Infant and Toddler Development 14 or the Ages and Stages Questionnaire 15 ). For example, maternal dietary intake during lactation can directly influence the nutritional composition of HM 16 with long-term consequences for infants 1 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Specific to cognition, maternal fish consumption leads to higher docosahexaenoic acid (DHA) concentrations in HM, which in turn has been linked to infant brain development 17 even if it is unclear whether this relationship influences infant growth in general 3 , 18 . Maternal characteristics such as age, body composition 12 , and socioeconomic status (e.g., maternal education or income) have been associated with infant growth and head circumference 4 . Similarly, maternal smoking habits can negatively influence infant growth 5 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Exclusive breastfeeding is the optimal feeding method for nearly all infants from birth to 6 months, and the health benefits that breastfeeding imparts on infants, children, and parents are well‐known 1–6 . However, numerous barriers deter many individuals from initiating and continuing to breastfeed 7–15 .…”
Section: Introductionmentioning
confidence: 99%
“…Exclusive breastfeeding is the optimal feeding method for nearly all infants from birth to 6 months, and the health benefits that breastfeeding imparts on infants, children, and parents are well-known. [1][2][3][4][5][6] However, numerous barriers deter many individuals from initiating and continuing to breastfeed. [7][8][9][10][11][12][13][14][15] The Centers for Disease Control and Prevention reported that in 2018, approximately 83% of birthing women ever breastfed, but approximately 47% at 3 months, and approximately 26% were exclusively breastfeeding at 6 months.…”
Section: Introductionmentioning
confidence: 99%